Renormalization-group calculation of dynamical properties for impurity models - Oliveira, L. N.; Líbero, V. L.; Frota, H. O.; Yoshida, M. [UNESP] (Elsevier B.V., 1991)
The numerical renormalization-group method was originally developed to calculate the thermodynamical properties of impurity Hamiltonians. A recently proposed generalization capable of computing dynamical properties is discussed. As illustrative applications, essentially exact results for the impurity specttral densities of the spin-degenerate Anderson model and of a model for electronic tunneling between two centers in a metal are presented. © 1991.
Keywords: Mathematical Techniques--Numerical Analysis; Thermodynamic Properties; Anderson Model; Impurity Models; Metals and Alloys